ANALISIS TERHADAP PERBEDAAN PENGHULU DALAM PENETAPAN WALI PADA PERNIKAHAN DI KUA KECAMTAN - Zainal Abidin (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
Marriage guardianship is something that is very important and is one of the pillars of marriage. Because the existence of a wali will determine whether a marriage is valid or not. There are two types of guardians in marriage, namely guardians nasab and guardians of judges. Guardianship or guardian in this marriage cannot be separated from nasab or hereditary problems, because with a legal marriage the aim is to maintain the nasab properly, regularly and uninterruptedly. In determining the marriage guardian, the headman has a very important role, which can determine whether a person can be guardian or not, and a marriage is with the guardian nasab or guardian judge. This research is a normative juridical research, with descriptive research type. The method of data collection is done by examining primary, secondary and tertiary legal materials and by making questionnaires to the princes by random means. The method used is descriptive qualitative analysis. The results showed that the prelates were in the same trusteeship issue with the determination of different guardians. The head of the District Aagama Affairs Office stipulates with the guardians of nasab while the other head of the District Office of Religious Affairs determines with the guardians of judges, there is even a determination of trustees based on the results of deliberations between the headman, bride and parents, according to the conscience and awareness of the parties. This can occur because the Marriage Law has not yet explicitly stipulated the determination of guardians, so the princes set it with understanding.